The effect of using the reciprocal learning method in performing the correction skill from jumping high and jumping in front with handball for female students aged (13-14) years in Baghdad - Sadi Jaber, Suaad (International Journal of Psychosocial Rehabilitation, 2020)
Handball is considered one of the differential games that have witnessed a wide spread in recent times because of the fun and excitement it carries in technical performance in addition to the many skills it contains in defense and attack, including the two correction skills, namely jumping high and jumping in the face of handball, which is one of the most important handball skills due to the fact that the team is And through it, he can advance to the opposing team by scoring a direct goal with it, and the importance of the research is that it is an experimental attempt by the researcher to lay educational foundations to master the skill of correction through some corrections such as jumping high and jumping in front of handball in a reciprocal manner, and given that the educational process improves the performance of skills in any game, The researcher decided to deal with research and study by introducing an interactive methodology in teaching the right skill. Ion from high jumping and jumping in front of handball for students of 13-14 years old in Baghdad governorate, and the research aims to:1. Identify the effect of using the interactive method in improving the skill of correcting the high jump rotary hand for female students (13–14) in Baghdad governorate.2. Identify the effect of using the interactive method in improving the shooting jump by the front hand for female students (13–14) years old in Baghdad governorate.